2019
DOI: 10.1515/biol-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of VAX2 restrains the malignant progression of papillary thyroid carcinoma by modulating ERK signaling pathway

Abstract: ObjectiveVentral anterior homeobox 2 (VAX2) gene is a key regulating factor for the development of the ventral region of the eye, and has recently attracted much attention from the cancer treatment field. Our study aimed to explore the effect of VAX2 on papillary thyroid carcinoma (PTC).MethodsWe determined the expression levels of VAX2 in PTC based on The Cancer Genome Atlas (TCGA) database. We then assessed the prognosis of patients with PTC, and analyzed the association between VAX2 expression and clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…SIX1 has been shown to be upregulated in thyroid cancers and associated with tumor size and metastasis 70 . Papillary thyroid carcinomas show an upregulation in VAX2 71 , and its development is facilitated by CERS6 72 . HHEX is considered a tumor suppressor gene in the thyroid and plays a crucial role in development of the gland 73 .…”
Section: Discussionmentioning
confidence: 99%
“…SIX1 has been shown to be upregulated in thyroid cancers and associated with tumor size and metastasis 70 . Papillary thyroid carcinomas show an upregulation in VAX2 71 , and its development is facilitated by CERS6 72 . HHEX is considered a tumor suppressor gene in the thyroid and plays a crucial role in development of the gland 73 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have documented the dysregulated expression of transcription factor genes in diverse cancer types, including GC [ 7 , 35 , 36 ]. Previous studies have reported that proteins from transcription factor genes regulate lncRNA transcription during tumor progression [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Norgett et al reported that VAX2 may be associated with distal renal tubular acidosis [ 38 ]. Furthermore, the depletion of VAX2 significantly inhibits the proliferation, migration, and invasion of PTC cells [ 7 ]. However, the function and mechanism of VAX2 in GC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventral Anterior Homeobox 2 (VAX2) is a transcription factor that regulates the dorsoventral specifica-tion of the forebrain and Wnt signaling [32,33]. The VAX2 has recently attracted many attentions in cancers and has been proved to regulate the malignant progression of thyroid cancer [34], breast cancer [35], and bladder cancer [36]. Src Homology 2 Domain Containing Transforming Protein (SHD) was over expressed in the cortex and frontal cortex, having a close relationship with spinal muscular atrophy type IV.…”
Section: Discussionmentioning
confidence: 99%